Policy Mechanism for Security of National Vital Objects in the Telecommunications Sector in Indonesia - Ariprawira, galih; Aji, Lessy Sutiyono; Wahyudin, Ade; Hikmaturokhman, Alfin (Buletin Pos dan Telekomunikasi, 2023)
Telecommunication infrastructure is part of critical infrastructure because it has a vital role in the community and affects the country's economy. Therefore, telecommunications infrastructure can be classified as a vital national object, requiring a particular security mechanism in its deployment. However, telecommunication infrastructure has different characteristics than other sectors, where the operation is fixed and mobile. Using a descriptive-analytical approach, data is obtained from benchmarks and interviews with resource persons from various fields through several Forum Group Discussion activities. Each telecommunications network operator can apply for National Vital Objects in the Telecommunications Sector based on the mechanism under the guidelines for determining the national vital object in the telecommunications sector stipulated through a Ministerial Regulation. The regulation covers various aspects, including the mechanism for determining, evaluating, fostering, and responsibilities of National Vital Objects in the Telecommunications Sector. In its implementation, the National Vital Objects in the Telecommunications Sector manager coordinates with various security parties, such as the Indonesian National Police. With the policy of the National Vital Objects in the Telecommunications Sector implementation mechanism, it is hoped that the telecommunications infrastructure can be well protected so that the business climate of telecommunications operations remains conducive and telecommunications services can always support the development and strengthening of the national economy.